Avaliação da Aderência em Estruturas Tubulares Metálicas Revestidas com Material Cimentício sob Esforços estáticos e dinâmicos. - Silva, Elisângela Pereira da (2010)
The bond on tubular steel coated with cementitious material, such as oil wells is quite complex. These are subject to change in temperature, pumping, steam injection, vibration caused by explosive charges, which can harm the interface of the tube cement paste through the loss of bond. Pullout tests in the laboratory are used for verification of the bond. However, this technique does not contemplate the life of the structural integrity of the well. This work aimed to contribute to the improvement of the technical verification of the bond through static and dynamic loading. For this, first using pullout tests has been proposed a study to test an improved speed of application loading. For this we used tubes coated partially of cement paste. Simulating the two contact conditions: no treatment on the surface of the tubes, and treatment with NaCl. It was observed that the presence of NaCl and a slower rate of load application positively influenced the bond stress. For the quasi-static dynamic test, by counting the number of cycles, it was felt that this substance in the interface showed a greater number of cycles. Thus it was concluded that this technique is feasible to evaluate the useful life of the well oil.